O EEG na insuficiencia renal cronica. II. Atividades paroxisticas - Speciali, J. G. [UNESP]; Resende, Luiz Antonio de Lima [UNESP]; Guimaraes Fonseca, R. [UNESP] (My University, 1997)
The authors describe paroxismal epileptiform EEG abnormalities in patients with chronic renal failure. One patient presented paroxismal epileptiform abnormalities in the right parietal region which proceded partial oculo-clonic motor seizures followed by a stroke localized in the same region. This was the main electroclinical correlation found, which, however, was not observed in other patients. Dialysis sessions may improve or worsen these paroxismal epileptiform abnormalities.
EEG in chronic renal failure. II. Paroxysmal epileptiform abnormalities
Keywords: chronic renal failure; EEG; adult; child; chronic kidney failure; electroencephalogram; epileptic discharge; focal epilepsy; human; major clinical study